Effect of β-Lactam Antibiotics on In Vitro Peptidoglycan Cross-Linking by a Particulate Fraction from Escherichia coli K-12 and Bacillus megaterium KM - Oka, Tetsuo (1978)
The binding constants of several β-lactam antibiotics towards penicillin-binding components in Escherichia coli K-12 (Spratt, Eur. J. Biochem. 72:341–352, 1977) and the antibiotic concentrations required to inhibit the peptidoglycan transpeptidase of E. coli 50% were compared. Penicillin-binding component 1B may have been the transpeptidase working in vitro. The structure-activity relationships of β-lactam antibiotics and the mechanisms of action in E. coli and Bacillus megaterium are discussed.